Social Relations and the Life Course
XII, 233 p.
Keywords: This collection of essays represents some of the most important recent research into changing patterns of family, household and community life. It brings together some of the leading sociologists in the field to explore how these informal social relationships change over time and the life course. It will be essential reading on courses concerned with the family and youth sociology.